Potensi Metformin sebagai Agen Anti-Kanker - Ni Made Dewi Puspita Sari; Muhartono; M. Yusran (CV. Jasa Sukses Abadi, 2019)
Metformin is one of the often prescribed anti-diabetic drugs. As an anti-diabetes effect, metformin also becomes anti-cancer. The mechanism of metformin as an anti-cancer through direct and indirect effects. Indirect sugar with loss of glucose levels, effects of hyperinsulinemia, levels of Insulin Growth Factor-1 (IGF-1), and immune responses to cancer cells. A direct effect on AMPK activation stimulation which works molecularly on cancer cells. This makes the metformation is potential as an anti-cancer agent alone or in combination with other chemotherapy agents or radiation.